Synthesis of 2′‐Fluorinated Northern Methanocarbacyclic (2′‐F‐NMC) Nucleosides and Their Incorporation Into Oligonucleotides. Issue 1 (27th January 2020) - Akabane‐Nakata, Masaaki; Kumar, Pawan; Erande, Namrata D.; Matsuda, Shigeo; Manoharan, Muthiah
Abstract: This article describes chemical synthesis of 2′‐fluorinated Northern methanocarbacyclic (2′‐F‐NMC) nucleosides and phosphoramidites, based on a bicyclo[3.1.0]hexane scaffold bearing all four natural nucleobases (U, C, A, and G), and their incorporation into oligonucleotides by solid‐supported synthesis. This synthesis starts from commercially available cyclopent‐2‐en‐1‐one to obtain the fluorinated carbocyclic pseudosugar intermediate (S.13 ), which can be converted to the uridine intermediate by condensation with isocyanate, followed by cyclization, and to adenine and guanine precursors by microwave‐assisted reactions. All four 2′‐F‐NMC phosphoramidites are synthesized from S.13 in a convergent approach, and the monomers are used for synthesis of 2′‐F‐NMC‐modified oligonucleotides. © 2020 by John Wiley & Sons, Inc. Basic Protocol 1 : Preparation of fluorinated carbocyclic pseudosugar intermediate Basic Protocol 2 : Preparation of 2′‐F‐NMC uridine and cytidine phosphoramidites Basic Protocol 3 : Preparation of 2′‐F‐NMC adenosine phosphoramidite Basic Protocol 4 : Preparation of 2′‐F‐NMC guanosine phosphoramidite Basic Protocol 5 : Synthesis of oligonucleotides containing 2ʹ‐F‐NMC